High quality planting stock - has research made a difference? - Ng, F.S.P. (Center for International Forestry Research, 1996)
Thirty years of research on planting stock in Malaysia, coveting the period of a FAO/UNDP pine project, an enrichment planting effort with dipterocarps in natural forest and a compensantory plantation project with fast growing trees, had minimal effect on the course of events. The pine project and the enrichment planting project were both given up after about 75 years of effort and the compensatory plantation project is likely to end in the same way. The interface between research and application was more complicated than what managers and scientists were prepared for and the benefit of research were seldom realized.